2020
DOI: 10.1038/s41598-020-74673-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of advanced glycation end products with sarcopenia and frailty in chronic kidney disease

Abstract: Prevalence of sarcopenia is high in patients with chronic kidney disease (CKD), especially in those with dialysis. Various pathological conditions related to CKD, such as chronic inflammation, insulin resistance, and endothelial dysfunction, are thought to be associated with the development and progression of sarcopenia. Advanced glycation end products (AGE), one of the representative uremic toxins, have been shown to contribute to various CKD-associated complications. This study investigated the role of AGE i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 64 publications
0
51
0
Order By: Relevance
“…this figure was modeled on data in refs. [33][34][35]180 . 212 , including delirium, for example, by applying cognitive screening, physical and social measures for delirium prevention, and reducing medications likely to increase delirium risk 213 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…this figure was modeled on data in refs. [33][34][35]180 . 212 , including delirium, for example, by applying cognitive screening, physical and social measures for delirium prevention, and reducing medications likely to increase delirium risk 213 .…”
Section: Discussionmentioning
confidence: 99%
“…These cellular and subcellular modifications are also graded by the degree of frailty. Clinical studies where the degree of frailty is quantified as the frailty phenotype have similarly shown that advanced glycation end products (AGEs) that arise in chronic kidney disease bind to receptors in skeletal muscle 180 . This leads to capillary rarefaction that may contribute to sarcopenia and physical frailty 180 .…”
Section: Frailty From Molecular To Organismal Scalesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that not only serum AGEs but also dietary AGEs are likely to be deposited in the gastrointestinal tract tissue and lead to the disruption of the microbiota (Figure 1) [29]. Given that dysbiosis is related to CKD progression, excessive intake of AGEs is likely to advance the progression of CKD and its comorbidities such as nerve system disorder [121], bone mineral disorder [122], cardiovascular diseases [12], and sarcopenia [123], possibly via the induction of dysbiosis. Mastrocola et al explored the impact of an AGEs-enriched diet on inflammation, as well as on the composition of gut microbiota in mice.…”
Section: Ages and Dysbiosis In Ckdmentioning
confidence: 99%
“…HMGB1 is released passively from necrotic injured cells or actively by immune cells, such as monocytes, and it works as a putative danger signal involved in pyroptosis and lethality in LPSinjected septic mice via the interaction with receptor for advanced glycation end products (RAGE), the other type of PRR [10][11][12][13][14]. We have recently found that the DNAaptamer raised against RAGE (RAGE-aptamer) significantly blocks the binding of advanced glycation end products (AGEs), senescent macroprotein derivatives formed at an accelerated rate under diabetes, to RAGE and resultantly attenuates development and progression of experimental diabetic nephropathy, melanoma growth and metastasis, and renal and muscle injuries in animal models of chronic kidney disease [15][16][17][18][19][20]. However, effects of RAGE-aptamer on lethality and organ damage in septic mice remain unclear.…”
Section: Introductionmentioning
confidence: 99%